2015
DOI: 10.4103/0970-2113.156241
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary hydatidosis in a tertiary care hospital

Abstract: Background:Hydatid disease is caused by the larval stage of Echinococcus. Liver is the most commonly involved organ followed by the lungs. Pulmonary hydatidosis can be primary or secondary. The disease may be asymptomatic for several years. Cause of concern is the fatal anaphylaxis, which may be life threatening.Materials and Methods:The present retrospective study is over a period of ten years (2003-2012). The demographic data including the clinical features, radiological findings, other organ involvement, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Moreover, a retrospective study analysing data over 10 years from Punjab, India, had found 8 patients with pulmonary hydatidosis, with six of them having solitary cysts while other two had bilateral lung involvement. Three have had associated cysts in the liver and spleen, while 4 had been treated with surgical lung lobectomies (10). Another case report by Teo et al describes a rare solitary pulmonary hydatid cyst in a 37-year-old Indian lady from Singapore, where she had presented with allergic manifestations following a rupture of the cyst and hydatid fluid leakage (6).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a retrospective study analysing data over 10 years from Punjab, India, had found 8 patients with pulmonary hydatidosis, with six of them having solitary cysts while other two had bilateral lung involvement. Three have had associated cysts in the liver and spleen, while 4 had been treated with surgical lung lobectomies (10). Another case report by Teo et al describes a rare solitary pulmonary hydatid cyst in a 37-year-old Indian lady from Singapore, where she had presented with allergic manifestations following a rupture of the cyst and hydatid fluid leakage (6).…”
Section: Discussionmentioning
confidence: 99%
“…Large cysts require certain management of the residual space to avoid postoperative dissemination through air and formation of empyema. 19 , 20 …”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary echinococcosis (PE) is a variant of the disease, in which parasites form lesions in the lungs. The pathogenesis of PE may involve bypassing the liver (primary PE) or metastatic-like spread from the liver (secondary PE) [ 2 ]. Primary or secondary PE is a clinically challenging condition in which anthelminthic regiments are important, but surgery has the central role in removing the cysts and preventing recurrences [ 3 ].…”
Section: Introductionmentioning
confidence: 99%